2014
DOI: 10.1074/jbc.m113.521773
|View full text |Cite
|
Sign up to set email alerts
|

A Disease-causing Mutation Illuminates the Protein Membrane Topology of the Kidney-expressed Prohibitin Homology (PHB) Domain Protein Podocin

Abstract: Background: Mutations in the stomatin family protein podocin are the most common genetic cause of proteinuria. Results: A conserved proline residue of podocin is essential for its membrane topology. Conclusion: This study confirms a hairpin-like structure of the membrane-attached PHB domain protein and its significance for cholesterol recruitment. Significance: Podocin P118L elucidates the pathogenic implication in kidney disease and identifies a novel family of PHB domain proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 39 publications
4
35
0
2
Order By: Relevance
“…However, a small part of the Pod wt pool was also glycosylated, consistent with the observations of WT podocin and stomatin by other authors (11,12). We tested by immunoblot the protein expression pattern of a series of podocin mutants that present different subcellular localizations, confirming that only ERretained mutants, such as Pod R168C , were enriched in N-glycosylated forms ( Figure 1E).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…However, a small part of the Pod wt pool was also glycosylated, consistent with the observations of WT podocin and stomatin by other authors (11,12). We tested by immunoblot the protein expression pattern of a series of podocin mutants that present different subcellular localizations, confirming that only ERretained mutants, such as Pod R168C , were enriched in N-glycosylated forms ( Figure 1E).…”
Section: Resultssupporting
confidence: 73%
“…To test whether the difference in protein levels of Pod wt and Pod R138Q was due to these differential glycosylation patterns, we also created podocyte cell lines stably expressing HA-tagged Pod wt and Pod R138Q bearing mutations in the amino acid residues required for Nglycosylation, N199 and N355 (Pod wt(N 199Q, N 355S) and Pod R138Q(N 199Q, N 355S) ). Immunoblots of protein extracts from these cells revealed that although the podocin triplet disappears with mutation of residues N199 and N355 ( Figure S1B), glycosylation alone does not account for the differences in protein levels of Pod wt and Pod R138Q , as there remains increased amounts of Pod wt(N 199Q, N 355S) compared to Pod R138Q(N 199Q, N 355S) .Our results showed that the mutant Pod R138Q was predominantly N-glycosylated, similarly to Pod P118L (12), another ER-retained podocin 2 by guest on May 10, 2018 http://www.jbc.org/ Downloaded from Podocin R138Q quality control and ERAD mutant, suggesting that the majority of intracellular Pod R138Q has a transmembrane topology (11,12). However, a small part of the Pod wt pool was also glycosylated, consistent with the observations of WT podocin and stomatin by other authors (11,12).…”
mentioning
confidence: 48%
See 3 more Smart Citations